1985
DOI: 10.1073/pnas.82.20.6850
|View full text |Cite
|
Sign up to set email alerts
|

Effect of magnetic fields on the triplet state lifetime in photosynthetic reaction centers: Evidence for thermal repopulation of the initial radical pair

Abstract: The lifetime of the molecular triplet state formed by recombination of the radical ion pair in quinonedepleted bacterial photosynthetic reaction centers is found to depend on applied magnetic field strength. It is suggested that this magnetic field effect results from thermally activated repopulation of the same radical ion pair that generates the triplet. Consistent with this hypothesis, the magnetic field effect on the triplet lifetime disappears at low temperature where the triplet state decays exclusively … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
45
0

Year Published

1986
1986
2014
2014

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 79 publications
(55 citation statements)
references
References 20 publications
(29 reference statements)
10
45
0
Order By: Relevance
“…This time constant is similar to those measured for the decay of pR in Q-depleted and Q--containing RCs (18,19). Debus et al (13) have reported a similar 28-ps component in their flash experiments, and they also have detected PR in EPR studies.…”
Section: Resultssupporting
confidence: 66%
“…This time constant is similar to those measured for the decay of pR in Q-depleted and Q--containing RCs (18,19). Debus et al (13) have reported a similar 28-ps component in their flash experiments, and they also have detected PR in EPR studies.…”
Section: Resultssupporting
confidence: 66%
“…Because the absorption bands for the monomeric chromophores overlap substantially and one expects vibronic bands from the special pair in this region, it is difficult to quantitate IAL (19,20), and this shoulder has been ascribed by some to the Pt Be chargetransfer state (20). Measurements of delayed fluorescence (21) and the temperature dependence of the 3P decay rate (22) for Rb. (Fig. 3C) (17) and some calculations (9 The value offJIAtI for the Qy transition of the special pair in both species decreases substantially when the temperature is decreased, while that for the other bands decreases considerably less.…”
Section: Resultsmentioning
confidence: 99%
“…Magnetic field modulated ISC has been detected in the photoconductivity [71][72][73], photoluminescence [74], excited state lifetime [75,76], and chemical reactivity [68] of many molecular systems, and even in the dynamics of photosynthesis in plants [77]. Magnetic field effects on the reaction outcome are already known for dozens of photochemical processes.…”
Section: Nanomagnetic Catalysismentioning
confidence: 99%